Combining Genome-Wide Gene Expression Analysis (RNA-seq) and a Gene Editing Platform (CRISPR-Cas9) to Uncover the Selectively Pro-oxidant Activity of Aurone Compounds Against Candida albicans - Alqahtani, Fatmah M.; Handy, Scott T.; Sutton, Caleb L.; Farone, Mary B. (Frontiers in Microbiology, 2021)
Candida albicans is the major fungal cause of healthcare-associated bloodstream infections worldwide with a 40% mortality rate. The scarcity of antifungal treatments due to the eukaryotic origin of fungal cells has challenged the development of selectively antifungal drugs. In an attempt to identify novel antifungal agents, aurones SH1009 and SH9051, as synthetically bioactive compounds, have been recently documented as anti-Candida agents. Since the molecular mechanisms behind the inhibitory activities of these aurones in C. albicans are unclear, this study aimed to determine the comprehensive cellular processes affected by these aurones and their molecular targets. Genome-wide transcriptional analysis of SH1009- and SH9051-treated C. albicans revealed uniquely repressed expression in different metabolic pathways, particularly trehalose and sulfur amino acid metabolic processes for SH1009 and SH9051, respectively. In contrast, the most commonly enriched process for both aurones was the upregulation of RNA processing and ribosomal cleavages as an indicator of high oxidative stress, suggesting that a common aspect in the chemical structure of both aurones led to prooxidative properties. Additionally, uniquely induced responses (iron ion homeostasis for SH1009 and arginine biosynthesis for SH9051) garnered attention on key roles for the aurone functional groups. Deletion of the transcription factor for the trehalose biosynthesis pathway, Tye7p, resulted in an SH1009-resistant mutant, which also exhibited low trehalose content, validating the primary molecular target of SH1009. Aurone SH9051 uniquely simulated an exogenous supply of methionine or cysteine, leading to sulfur amino acid catabolism as evidenced by quantifying an overproduction of sulfite. Phenyl aurone, the common structure of aurones, contributed proportionally in the prooxidative activity through ferric ion reduction effects leading to high ROS levels. Our results determined selective and novel molecular mechanisms for aurone SH1009 and also elucidated the diverse cellular effects of different aurones based on functional groups.